Plant embryogenesis requires AUX/LAX-mediated auxin influx - Robert, Hélène S; Grunewald, Wim; Sauer, Michael; Cannoot, Bernard; Soriano, Mercedes; Swarup, Ranjan; Weijers, Dolf; Bennett, Malcolm; Boutilier, Kim; Friml, Jiří (Development (Cambridge, England), 2015)
The plant hormone auxin and its directional transport are known to play a crucial role in defining the embryonic axis and subsequent development of the body plan. Although the role of PIN auxin efflux transporters has been clearly assigned during embryonic shoot and root specification, the role of the auxin influx carriers AUX1 and LIKE-AUX1 (LAX) proteins is not well established. Here, we used chemical and genetic tools on Brassica napus microspore-derived embryos and Arabidopsis thaliana zygotic embryos, and demonstrate that AUX1, LAX1 and LAX2 are required for both shoot and root pole formation, in concert with PIN efflux carriers. Furthermore, we uncovered a positive-feedback loop between MONOPTEROS (ARF5)-dependent auxin signalling and auxin transport. This MONOPTEROS-dependent transcriptional regulation of auxin influx (AUX1, LAX1 and LAX2) and auxin efflux (PIN1 and PIN4) carriers by MONOPTEROS helps to maintain proper auxin transport to the root tip. These results indicate that auxin-dependent cell specification during embryo development requires balanced auxin transport involving both influx and efflux mechanisms, and that this transport is maintained by a positive transcriptional feedback on auxin signalling.
Keywords: Arabidopsis thaliana embryogenesis; biologický transport; signální transdukce; LIKE-AUX1 (LAX); kyseliny indoloctové; Biological Transport; Indoleacetic Acids; Signal Transduction; Seeds; Auxin transport; AUX1; rostlinné proteiny; Microspore; semena rostlinná; Plant Proteins; Brassica napus; MONOPTEROS (ARF5); PIN; Arabidopsis